Implementation of Gender Responsive Policies in Higher Education: A Study at Three Universities in North Sumatra - Yurisna Tanjung; Mujahiddin Mujahiddin; Ida Martinelli (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
One of the problems that are often faced related to the implementation of Gender Mainstreaming in Higher Education is Do Higher Education Have Policies, Programs, Activities, and Budgeting by paying attention to the needs of men and women in the Governance of the Tridharma of Higher Education through the Gender Mainstreaming Strategy. Based on these conditions, the purpose of this study is to find out whether universities have Gender Responsive Policies, Programs, Activities and Budgeting to build gender sensitivity and commitment of policy makers to make Higher Education Gender Responsive.  In addition, this research will produce publications in accredited national journals in Sinta-2 and additional outputs in the form of Copyright in the form of books with ISBN. The research method uses a qualitative research design with a case study approach. Where the subject of this research will be taken with a purposive sampling approach. The primary data collection techniques used in-depth interviews and documentation. The collected data is then analyzed using a qualitative approach with an interactive model as proposed by Miles and Huberman, namely; Data reduction, data presentation, and conclusion drawing/verification.The results of the research show firstly that the three universities representing universities in the city of Medan in general have not yet become gender-responsive universities. This can be seen from the absence of policies, programs, activities and budgets that accommodate the needs of all lines, both men, women, children, disabilities and others. Second, the lack of gender sensitivity and commitment from policy makers to make it a Gender Responsive University. ThirdPSGA does not yet have a role in providing understanding to structural officials and the academic community about the formation and development of Gender Responsive Higher Education. However, one thing that attracts Islamic universities is to implement gender-responsive universities.